Crime by Policewomen in the United States, 2005-2014 - Stinson, Philip M (2019)
This study is a replication and extension of Stinson, Todak, and Dodge’s (2015) study of crime by policewomen across the United States in years 2005-2007. The sample for the current study includes 597 arrest cases involving 555 female police officers, each of whom were arrested during the decade 2005-2014. The arrested female officers were employed by 353 state and local law enforcement agencies located in 273 counties and independent cities within 44 states and the District of Columbia. Findings indicate that crimes committed by policewomen are most often violence-related, alcohol-related, and/or profit-motivated offenses. Descriptive and bivariate statistics are reported on variables of interest. Additional findings report differences between crimes committed by policemen and policewomen. Presented at the American Society of Criminology Annual Meeting in San Francisco, CA